Nitric oxide, interorganelle communication, and energy flow: a novel route to slow aging - Valerio, Alessandra; Nisoli, Enzo (Frontiers in Cell and Developmental Biology, 2015)
The mitochondrial lifecycle (mitochondrial biogenesis, dynamics, and removal by mitophagy) is carefully orchestrated to ensure the efficient generation of cellular energy and to maintain reactive oxygen species production within an optimal range for cellular health. Based on latest research, these processes largely depend on mitochondrial interactions with other cell organelles, so that the ER- and peroxisome-mitochondrial connections might intervene in the control of cellular energy flow. Damaged organelles are cleared by autophagic mechanisms to assure the quality and proper function of the intracellular organelle pool. Nitric oxide (NO) generated through the endothelial nitric oxide synthase (eNOS) acts a gas signaling mediator to promote mitochondrial biogenesis and bioenergetics, with a favorable impact in diverse chronic diseases of the elderly. Obesity, diabetes and aging share common pathophysiological mechanisms, including mitochondrial impairment and dysfunctional eNOS. Here we review the evidences that that eNOS-dependent mitochondrial biogenesis and quality control, and possibly the complex interplay among cellular organelles, may be affected by metabolic diseases and the aging processes, contributing to reduce healthspan and lifespan. Drugs or nutrients able to sustain the eNOS-NO generating system might contribute to maintain organelle homeostasis and represent novel preventive and/or therapeutic approaches to chronic age-related diseases.